Pemanfaatan Produk Google Serta Situs PHET (Physics Education Technology) Sebagai Media Pembelajaran Fisika Berupa Stimulus - Huzaima Mas’ud; Maemunah M (Al-Ishlah: Jurnal Pendidikan Islam, 2022)
Education is one of the needs that must be met, where education is a process that will develop self-potential. Covid-19 has had a huge impact in various fields, one of which is in the field of education. This outbreak requires a change in the learning process that previously met face to face in class to distance learning which is carried out online. Teachers as educators must be good at utilizing existing technology to develop learning media in an effort to create an interactive learning. One of the problems that are often encountered in making learning media is practical learning on physics materials. One example is the creation of media using Google products and the “PhET (Physics Education Technology)” website. Physics learning is in the form of products (outcomes) such as concepts, principles, laws and theories so that media are needed to achieve these characteristics. Simulations in PhET are interactive and designed in an animation-like form to make it easier to do practicals. PhET already has more than 100 simulations of learning materials that can be used in various lessons. This study aims to describe the use of Physics learning media in the form of web-based electronic modules PhET (Physics Education Technology) using Google Sites on physics material. The method used in this study is a literature study method, literature review with the source of the data obtained is a secondary data source. This learning media is designed to help students learn independently.